The intermediary bank within the framework of the rules of banking governance - Amir, Yassir; Nafea, Khales (Journal of Legal Sciences, 2022)
The stok marker is a welcoming space for expense work as a broker who practices securities trading for the benefit of its clients, and since the broker as a legal person is a bank , so this research was necessary to review the banking governance rules that apply to the brocker, both at the level of appointment and selection, and what are the conditions that They must be present in the personality of the mediator and his assistants, or the application of the rules of banking governance either directly or indirectly.